Relationships of the Big Five Personality with Self-Esteem and Emotion Understanding in Students from Visual Arts High Schools and General Education High Schools - Kuśpit, Małgorzata; Tychmanowicz, Anna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2022)
The problem of the present study was defined as follows: What personality characteristics were predictors of emotion understanding and self-esteem in students of visual arts high schools and general education high schools. The problems discussed in this article have important implications for the effective functioning of artistically gifted youth in the school environment and for the optimization of their development in various areas of activity. Students of visual arts and general education high schools (N = 440) aged 15–18 (M = 16.88, SD = 0.81) in Poland were surveyed. The participants completed Costa and McCrae’s NEO-FFI, Rosenberg’s Self-Esteem Scale (SES), and Matczak and Jaworowska’s Emotion Understanding Test (TRE). Enter regression analysis was conducted. The results showed that in the group of visual arts high school students neuroticism, extraversion, and conscientiousness were significant predictors of self-esteem, while neuroticism and openness to experience were predictors of emotion understanding. In the group of high school students who pursued a general education curriculum, self-esteem was statistically significantly predicted by neuroticism and conscientiousness. Significant predictors of emotion understanding in this group of students included neuroticism, extraversion, openness to experience, and agreeableness. These findings demonstrate that the students functioned differently in the school setting depending on the educational curriculum they were following. The results of the present study can be used to formulate practical educational guidelines.